The Effect of Knowledge Enablers on Knowledge Management Process: A Case Study of Kolej Matrikulasi Perak, Kementerian Pelajaran Malaysia - Azura, Mat Russ (2009)
This study is undertaken to determine the effect of organizational elements on knowledge management process. Generally, the objective of this study is to determine the effects of knowledge management (KM) enablers namely strategic leadership, culture, information technology, HR activities on KM process. Based on previous studies, it is important to effectively and efficiently manage these organizational elements (KM enablers) in order to have a successful KM process. This study was conducted in Kolej Matrikulasi Perak, Kementerian Pelajaran Malaysia; an educational institution offering a pre-university program. This research is a cross-sectional research which uses a case study approach. The respondents of this study were the academic staffs of Department of Sciences, Mathematics and Arts. Questionnaires consisting five point Likert scale was used to measure how strongly respondents agree or disagree with the statements .In the case of Kolej Matrikulasi Perak, the most important factor affecting implementation of KM process is its human resource activities, followed by organizational culture and information technology. Based on the findings, the researcher suggests that the top management of this college to form a strong human resource policies in order to obtain full utilization of knowledge in the organization.